Specifics of english economic terminology translation - Khrystiuk, S. B. (НУБіП України, 2019)
Economic terms are considered to be one of the most dynamic parts of the lexical and semantic language system. Thus, taking into account that there are significant differences in the structure of the different countries economic systems, economic terms require the detailed study within one language and further comparison within two or more languages.
Особливості перекладу англійської термінологічної лексики в галузі економіки
Стаття присвячена дослідженню феномена розвитку сучасної української економічної термінології, пошуку адекватних та ефективних перекладацьких трансформацій, аналізу основних труднощів перекладу англомовних економічних термінів на українську мову. Доведено актуальність дослідження. Проаналізовано стан розробки наукової проблематики дослідження.
Keywords: globalization processes; economic terminology; translation; terminology unit; equivalent; calquing; transliteration; transcription